Vitamin D3 Attenuates Viral-Induced Inflammation and Fibrotic Responses in Bronchial Smooth Muscle Cells - Plesa, Maria; Gaudet, Mellissa; Mogas, Andrea; Jalaleddine, Nour; Halayko, Andrew; Al Heialy, Saba; Hamid, Qutayba (Frontiers in Immunology, 2021)
Toll-like receptor 3 (TLR3) activation by viral infections plays a key role in promoting inflammatory immune responses that contribute to pulmonary fibrosis in chronic inflammatory respiratory diseases. Vitamin D3 has been shown to be beneficial to patients with asthma and chronic obstructive pulmonary disease (COPD) through its anti-inflammatory and anti-fibrotic properties. Smooth muscle cells are one of the major contributors to airway remodeling in asthma and COPD. We therefore aimed to investigate the effect of vitamin D3 treatment on viral-induced TLR3 responses in Bronchial Smooth Muscle Cells (BSMCs) as a mechanism contributing to pulmonary fibrosis in asthma and COPD. Primary BSMCs from patients with asthma (n=4), COPD (n=4), and healthy control subjects (n=6) were treated with polyinosinic: polycytidylic acid (polyI:C), TLR3 agonist in the presence or absence of vitamin D3 (1,25D3). Here we report the mRNA expression and protein levels of pro-inflammatory and pro-fibrotic markers (IL-6, IFN-1, CCL2/MCP-1, fibronectin 1 and type I collagen) among BSMCs groups: asthma, COPD, and healthy controls. We show that at the baseline, prior to polyI:C stimulation, asthma and COPD BSMCs presented increased pro-inflammatory and pro-fibrotic state compared to healthy control subjects, as measured by quantitative PCR and immunoassays (ELISA/Flow Cytometry. Ligation of TLR3 by polyI:C in BSMCs was associated with increased TLR3 mRNA expression, and 1,25D3 treatment significantly reduced its expression. In addition, 1,25D3 decreased the expression of IL-6, IFN-1, CCL2, FN1 and COL1A1 induced by polyI:C in BSMCs. The regulatory effect of 1,25D3 treatment on polyI:C-stimulated BSMCs was further confirmed at protein levels. Our findings suggest that vitamin D3 attenuates TLR3 agonist-induced inflammatory and fibrotic responses in BSMCs and support the clinical relevance of vitamin D3 supplementation in patients with viral infections having chronic respiratory diseases, such as asthma and COPD.